Effect of Ethanol and Gasoline Blending on the Performance of a Stationary Small Single Cylinder Engine - Rao R.N.; Silitonga A.S.; Shamsuddin A.H.; Milano J.; Riayatsyah T.M.I.; Sebayang A.H.; Nur T.B.; Sabri M.; Yulita M.R.; Sembiring R.W. (Springer, 2023)
To reduce dependency on fossil fuel, alternative fuel may be considered either to replace fossil fuel or to improve the characteristics of fossil fuel. Ethanol is one of the alternative fuels that has been used as an additive to gasoline fossil fuel in many countries, particularly for spark ignition engine system. This research aims to investigate the effect of ethanol and gasoline blending on the performance of a non-road small single cylinder engine. Ethanolgasoline blends of different concentrations are considered in this paper, to experimentally compare their performances, under varying engine speed but constant engine load. The experimental results showed that the addition of ethanol to gasoline has improved the overall engine performance. High ethanolgasoline fuel blend (E40) is suitable for low engine speed, while low ethanolgasoline fuel blend (E10) can replace the neat gasoline without modification as their performance is very identical. 2020, King Fahd University of Petroleum & Minerals.